SAT0459 EVALUATION OF THE PREVALENCE AND THE MANAGEMENT OF OSTEOPOROTIC FRACTURES IN PATIENTS HOSPITALIZED AT NANCY UNIVERSITY HOSPITAL (FRANCE) IN 2017. (2nd June 2020) - Baccichetti, A.; Nguyen-Thi, P. L.; Blum, A.; Mainard, D.; Sirveaux, F.; Nace, L.; Valance, A.; Civit, T.; Dautel, G.; Perret-Guillaume, C.; Guerci, B.; Tronel, H.; et al.
Abstract : Background: Osteoporotic fractures are a major public health concern because of their consequences in morbidity, costs and mortality. In the meantime, historically postfracture osteoporosis medication use rates have been poor. Objectives: The aim is to analyze the management of osteoporosis in patients hospitalized for osteoporotic fractures (OF) at Nancy University Hospital (France) in 2017. Methods: Total number of hospitalized patients and hospital stays were extracted by the Department of Medical Information (DIM) which selected departments with at least forty hospitalizations with Medical Unit Summary related to a diagnosis of fracture or osteoporosis. Hospitalizations not concerned by a recent OF were excluded. Data on fractures, patient characteristics, risk factors for OF and fall, management of osteoporosis, discharge status, stay duration, were studied from patient medical records. Prevalence of OF stays, management of osteoporosis and factors associated with duration of stay were analyzed. Results: Out of a total of 153, 840 hospitalizations, 918 hospitalizations (844 patients, mean age 74.5 years ± 13.6, 74.5% women) concern an OF. The prevalence of hospitalizations for OF was 0.6% of total hospitalizations and 17.9% of total hospitalizations for fractures. Among the 844 patients, 85.7% had a severe fracture (vertebral fracture: 56.2%, hip fracture: 24.1%), 16.5% had a non-severe fracture, and 8.5% had a fracture cascade in the year. At discharge from hospital, 11.7% of patients received a specific treatment for osteoporosis. Longer stay duration was associated with age, severe fractures, Groll index and discharge status. Conclusion: Nearly one hospitalized fracture in five is osteoporotic, while only one in ten patients is treated for osteoporosis. Stay duration increased with age and comorbidities. This encourages the development of early prevention, screening and treatment strategies for osteoporosis. References: [1]Hernlund E, Svedbom A, Ivergård M, Compston J, Cooper C, Stenmark J, et al. Osteoporosis in the European Union: medical management, epidemiology and economic burden. A report prepared in collaboration with the International Osteoporosis Foundation (IOF) and the European Federation of Pharmaceutical Industry Associations (EFPIA). Arch Osteoporos. 2013;8:136. [2]Johnell O, Kanis JA. An estimate of the worldwide prevalence and disability associated with osteoporotic fractures. Osteoporos Int. 2006 Oct 19;17(12):1726–33. [3]Giangregorio L, Papaioannou A, Cranney A, Zytaruk N, Adachi JD. Fragility Fractures and the Osteoporosis Care Gap: An International Phenomenon. Semin Arthritis Rheum. 2006 Apr;35(5):293–305. Disclosure of Interests: None declared